Kilka uwag o Internetowej Platformie Aukcyjnej umożliwiającej uzyskanie wsparcia w zakresie odnawialnych źródeł energii w kontekście podpisów elektronicznych - Trupkiewicz, Marcin (Studia Prawa Publicznego, 2019)
The paper describes certain basic principles of the new system of supporting renewable energy sources (RES) introduced in Poland. The amended Polish Act on Renewable Energy Sources (Polish RES Act) has introduced an auction system which is a new legal instrument enabling the selection of RES generators with adequate ﬁ nancial support. Each Renewable Energy Sources project (RES plant project) to generate and sell electricity must go offi cially through an auction. The Internet Auction Platform is an IT tool used in the process. It en ables to conduct the pre-qualiﬁ cation procedure as well as to prepare the auction off er. This new solution has entailed certain legal issues that must be addressed such as the access to the IT system, electronic submission of tenders or the use of an electronic signature to conﬁ rm the statements made in the electronic procedure. All these issues have been discussed in this paper. The paper also contains an analysis of the diff erences between two possible forms of electronic signature that may be used in the process, and identiﬁ es the main advantages and disadvantages of either. It is then concluded that although the online RES auction could be more competitive, in the version as it is it allows to carry out an eff ective auction.